Biomimetic sensor based on 5,10,15,20-tetrakis(pentafluorophenyl)-21H,23H- porphyrin iron (III) chloride and MWCNT for selective detection of 2,4-D - Wong, Ademar [UNESP]; Sotomayor, Maria Del Pilar Taboada [UNESP] (Elsevier, 2013)
Exploitation of the electronic properties of carbon nanotubes for the development of voltammetric and amperometric sensors to monitor analytes of environmental relevance has increased in recent years. This work reports the development of a biomimetic sensor based on a carbon paste modified with 5,10,15,20-tetrakis(pentafluorophenyl)-21H,23H-porphyrin iron (III) chloride (a biomimetic catalyst of the P450 enzyme) and multi-wall carbon nanotubes (MWCNT), for the sensitive and selective detection of the herbicide 2,4- dichlorophenoxyacetic acid (2,4-D). The sensor was evaluated using cyclic voltammetry and amperometry, for electrochemical characterization and quantification purposes, respectively. Amperometric analyses were carried out at -100 mV vs. Ag/AgCl(KClsat), using a 0.1 mol L-1 phosphate buffer solution at pH 6.0 as the support electrolyte. Under these optimized analytical conditions, the sensor showed a linear response between 9.9 × 10-6 and 1.4 × 10-4 mol L-1, a sensitivity of 1.8 × 104 (±429) μA L mol -1, and limits of detection and quantification of 2.1 × 10 -6 and 6.8 × 10-6 mol L-1, respectively. The incorporation of functionalized MWCNT in the carbon paste resulted in a 10-fold increase in the response, compared to that of the biomimetic sensor without MWCNT. In addition, the low applied potential (-100 mV) used to obtain high sensitivity also contributed to the excellent selectivity of the proposed sensor. The viability of the application of this sensor for analysis of soil samples was confirmed by satisfactory recovery values, with a mean of 96% and RSD of 2.1% (n = 3). © 2013 Elsevier B.V.
Keywords: 2,4-D; Biomimetic sensor; Iron (III) Porphyrin; MWCNT; P450 enzyme; Biomimetic sensors; Iron porphyrin; P450 enzymes; Biomimetics; Carbon; Chlorine compounds; Cyclic voltammetry; Electronic properties; Enzymes; Herbicides; Multiwalled carbon nanotubes (MWCN); Porphyrins; Sensors